Analysis Analysis of the Role of the Agricultural Sector in the Economy of North Kalimantan Province 2015-2024 - Aisyah Fahzira; Dewi Rohma Wati (Universitas Veteran Bangun Nusantara, 2026)
The agriculture, forestry, and fisheries sector is an important primary sector in North Kalimantan Province, although its contribution and growth rate tended to decline over the 2015-2024 period. This study aims to analyze the role of the agricultural sector as a base sector, identify potential subsectors for the future, analyze the economic growth of the agricultural sector in North Kalimantan Province compared to the national agricultural sector's economic growth, and map its growth pattern and structure against the national level. The methods used are LQ, DLQ, Shift Share, and Klassen Typology. The LQ analysis results indicate that this sector constitutes a base sector (LQ = 1,43), with the forestry, fisheries, and horticulture subsectors obtaining LQ>1. The DLQ analysis reveals five prospective future subsectors, with the estate crops subsector recording the highest value. Through the Shift Share analysis, the sector demonstrates a positive trend with an increase in added value of IDR 3.8 trillion driven by national policies, despite growing at a slower pace than the national average. Furthermore, the agricultural sectors/subsectors in North Kalimantan Province can be classified into four categorie, developed and fast-growing sectors, developed but stagnant sectors, developing or potential sectors, and underdeveloped sectors. The agriculture, forestry, and fisheries sector as a whole, along with the forestry and fisheries subsectors, are categorized as developed and fast-growing (Quadrant I), whereas the food crops subsector falls into the underdeveloped category (Quadrant IV).